Community safety partnerships: the limits and possibilities of ‘policing with the community’ - Harkin, Diarmaid (Crime prevention and community safety, 2018)
Partnerships between the police and the wider community to tackle safety issues are a cornerstone of contemporary thinking about policing. Using data from two studies into community safety partnerships in Northern Ireland and Scotland, this article argues that the level of policing ‘with’ the community varies greatly depending on the particular safety issue that is being addressed. Using Osborne and Gaebler’s (Reinventing government: how the entrepreneurial spirit is transforming the public sector, Plume, New York, 1991) metaphor, I argue that there is a spectrum of issues that moves from inevitably high levels of unilateral police action where the police retain firm control over ‘steering’ and ‘rowing’ functions, towards issues that enjoy higher levels of police-community collaboration where ‘steering’ and ‘rowing’ can be shared more democratically. Outlining such a spectrum can help clarify the suitable expectations of what community safety partnerships can practically achieve.